Understanding Michel Foucault (1926-1984): Power, Sexuality, and Identity: An Exploration of Michel Foucault's Ideas (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this paper sexuality does not involve the denial of biological functions but tries to vision how deployments of power are directly connected to the body, history of bodies where biological and historical factor interconnect in complex relations. Sex was developed as an essential property underlying bodies and physiology. Sex was indispensable, theoretically for grouping anatomy, conduct, biology etc and pleasure for reifying a secret causality. Epistemology of sex gained momentum from its proximity to biology and biology provided principles of normalization. The idea of sex turned around or reversed the representation of power to sex, treating power as law and dominating sex. Sex is the most abstract creation of power. Sex serves access to one’s identity (nameless urge) and intelligibility (madness) leading to care and respect for sex a value stronger than life.